Fate of the oceans Part Two : protecting the oceanss - Perez, Ana Maria; LLagostera, Ferran; Films for the Humanities & Sciences (Princeton, NJ : Films for the Humanities & Science, 2007)
Although sustainable fishing practices are a rarity in our environmentally threatened world, some can be found. This program searches out fishing industries that take steps to protect delicate ecosystems...
Part One. Plendering the oceans -- Part Two. Protecting the oceans.
[Originally produced in 2005 as an episode of the Television Trust for the Environment's series Earth report].
Producer, Ferran LLagostera; editor, Ana Maria Perez ; series editor, Robert Lamb.
Narrator: Hilary Sandison.
DVD format.
Keywords: Overfishing; Ocean and civilization